The Decomposition and Uniqueness of $n$-Lie Superalgebras (Communications in Mathematical Research, 2021)
In this paper, the definitions and some properties of $n$-Lie superalgebras are presented. Our main aim is to study the decomposition and uniquenessof finite dimensional $n$-Lie superalgebras with trivial center. According to thedecomposition of $n$-Lie superalgebras, we obtain the decomposition of innerderivation superalgebras and derivation superalgebras respectively. Furthermore, we discuss some properties about the centroid of $n$-Lie superalgebras, sowe can see its application in the decomposition of $n$-Lie superalgebras.